Effect of Plant Growth Promoting Rhizobacteria in Cultivation of Tomato (Lycopersicum esculentum Mill.) - Meutia, Rizka Inda; Syafruddin, Syafruddin; Bakhtiar, Bakhtiar (Universitas Panji Sakti, 2024)
The effect of Plant Growth Promoting Rhizobacteria (PGPR) in tomato plants can impact plant growth and production with the relationship between bacteria and plant roots. This research aimed to decide the benefits and impacts of PGPR on the development and production of tomato plants. The research was conducted within the Research facility of Seed Science and Innovation of Agrotechnology Consider Program of Syiah Kuala University, Exploratory Plant of Staff of Horticulture, Syiah Kuala University from February 2023 to December 2023. This study used 2 designs, namely the Complete Randomized Design and Randomized Group Design of factorial pattern. Non-factorial RAL uses 1 factor studied, namely rhizobacterial isolates (R) consisting of one control treatment and five kinds of isolates. Factorial RACT was used to treat two tomato varieties consisting of Servo (V1) and Gammara (V2). Subsequently, 2x6 medications were obtained, each treatment was rehashed 3 times, hence 12 treatment combinations and 36 exploratory units were obtained, whereas each test unit utilized 3 plant tests so that there were 108 plants in add up to. If the results of the F test show significant influence, then the analysis continues with further testing using DMRT (Duncan Multiple Range Test) test at the 5% level. The results of the consider, that the arrangement of rhizobacteria as PGPR in tomato plant development does not have a noteworthy impact. The utilization of Servo and Gammara tomato plant assortments has a critical impact on tomato plant development.